′PEN′ appendicitis - Amadou Issa; Ngaringuem Olivier; Ndour Oumar; Ngom Gabriel (Wolters Kluwer Medknow Publications, 2010)
We report a three-year-old boy who ingested the tip of a pen and presented with signs of appendicitis. Plain abdominal radiographs showed the foreign body in the right iliac fossa. Surgical exploration revealed perforated appendix and the foreign body in its lumen. Appendectomy resulted in satisfactory recovery.